Are Labor-Managed Firms Really Able to Survive Competition With Profit-Maximizing Firms? - Luca Lambertini; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
The behaviour of labor managed and profit seeking firms in a Cournot duopoly with capital strategic interaction is analysed. Whena pure labor managed duopoly is considered, firms choose their capital commitments according to the level of the interest rate, unlike what usually happens when only profit maximizing firms operate in the market. If we consider a mixed duopoly, the profit maximizing firm underinvests as a reaction to the strategic asymmetry characterizing competition in the quantity stage regardless of the rental cost of capital, while the investment decision taken by the labor managed firm is again affected by the cost of capital. The nature of competition between a PM and an LM firm is such that the LM firm is induced to set her own capital in such a way that she does not enter the market.
Keywords: 330